THE EFFECT OF LEG MUSCLE STRENGTH TRAINING WITH BALLS ON THE LONG PASSING ABILITY OF THE SSB PUTRA BAYANG PLAYERS IN BAYANG DISTRICT PESISIR SELATAN REGANCY - Diki Saputra; Bafirman Bafirman; Hanif Badri (JURNAL STAMINA, 2019)
The research problem is the lack of long passing ability of the SSB Putera Bayang Players in Bayang District, Pesisir Selatan Regancy. This study aims to determine the effect of leg muscle strength training (single leg squat and close squat training) on ​​the long passing ability of the the SSB Putera Bayang Players in Bayang District, Pesisir Selatan Regancy. This type of research is quasi-experimental research. The population in this study were all players who were actively practicing at the Putera Bayang SSB in Bayang district, Pesisir Selatan regancy, which were 21 people. The sampling technique is the total sampling technique, then the sample of this study amounted to 21 people. The instrument in this study used a gastric passing test to measure long passing ability. Data analysis and hypothesis testing using comparative analysis techniques using different mean test formula (t test) with a significance level α = 0.05. From the data analysis performed, the results are obtained: There is the effect of Leg muscle strength training with the ball on the long passing ability the SSB Putera Bayang Players in Bayang District, Pesisir Selatan Regancy, with the acquisition of the "t" test coefficient that is t = 6.61> t table = 1.724.